(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
Diabetes mellitus is one of the most common non-communicable diseases globally. Magnitude of DM in developing countries including Bangladesh is rising rapidly. Several studies across the world have reported the association of higher serum hepatic enzyme levels with type 2 DM which may be an expression of excess deposition of fat in the liver. Thus, serum hepatic enzyme levels may serve as a marker of insulin resistance in the liver and may predict the prognosis and complications in type 2 DM individuals. The present crosssectional study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July’ 2015 to June’ 2016 to find out the association of serum hepatic enzyme levels with type 2 DM individuals in a tertiary level hospital. A total number of 100 subjects were selected with the age ranging from 30 to 60 years. Among them, 50 diagnosed type 2 DM individuals were included in the Group A and 50 apparently healthy individuals were selected as Group B for comparison. The study parameters were fasting plasma glucose (FPG), HbA1c, ALT, AST, ALP and GGT. The mean(±SD) serum ALT, AST, ALP and GGT concentration (U/L) in cases were 46.28±.81, 28.17±10.08, 118.26±16.08 and 36.98±10.08 respectively and mean(±SD) serum ALT, AST, ALP and GGT concentration(U/L) in controls were 29.54±8.56, 24.54±6.89, 96.68±14.36 and 23.82±6.98 respectively. The present study showed that higher levels of serum hepatic enzymes (ALT, AST, ALP and GGT) were present in subjects with type 2 diabetes mellitus. Among these parameters, ALT, ALP and GGT showed positive correlation with FPG and HbA1c in both groups but AST showed no correlation with FPG and HbA1c. Bangladesh J Med Biochem 2017; 10(2): 58-63